2018
DOI: 10.1074/jbc.ra118.004066
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of plasma membrane–associated phosphoinositides mimics inhibition of TRPM7 channels by cytosolic Mg2+, spermine, and pH

Abstract: Transient receptor potential cation channel subfamily M member 7 (TRPM7) is an ion channel/protein kinase belonging to the TRP melastatin and eEF2 kinase families. Under physiological conditions, most native TRPM7 channels are inhibited by cytoplasmic Mg2+, protons, and polyamines. Currents through these channels (ITRPM7) are robustly potentiated when the cell interior is exchanged with low Mg2+-containing buffers. ITRPM7 is also potentiated by phosphatidyl inositol bisphosphate (PI(4,5)P2) and suppressed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(56 citation statements)
references
References 76 publications
(139 reference statements)
4
51
0
Order By: Relevance
“…Several reports indicate that activation of phospholipase C (PLC) induces Ca 2+ influx via TRPM7 in intact cells (Langeslag et al ; Qian et al ). There are contradicting reports showing that TRPM7 is inactivated by G αq ‐coupled receptor stimulation via the PLC‐mediating depletion of phosphatidylinositol 4,5‐bisphosphates (PIP 2 ) which is necessary for TRPM7 channel activity (Runnels et al ; Kozak et al ; Gwanyanya et al ; Bates‐Withers et al ; Zhelay et al ). Therefore, the physiological stimuli that activate PLC in adipocytes might increase or decrease [Ca 2+ ] i by activation or inactivation of TRPM7.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports indicate that activation of phospholipase C (PLC) induces Ca 2+ influx via TRPM7 in intact cells (Langeslag et al ; Qian et al ). There are contradicting reports showing that TRPM7 is inactivated by G αq ‐coupled receptor stimulation via the PLC‐mediating depletion of phosphatidylinositol 4,5‐bisphosphates (PIP 2 ) which is necessary for TRPM7 channel activity (Runnels et al ; Kozak et al ; Gwanyanya et al ; Bates‐Withers et al ; Zhelay et al ). Therefore, the physiological stimuli that activate PLC in adipocytes might increase or decrease [Ca 2+ ] i by activation or inactivation of TRPM7.…”
Section: Discussionmentioning
confidence: 96%
“…activity (Miller et al, 2015;Nowicka-Bauer and Szymczak-Cendlak, 2021) and sperm tail VSP protein. The level of phosphorylation varies (Zhelay et al, 2018). Zhou et al (2015) found that total sperm motility and progressive motility were higher at pH 7.2 and 8.2 than at pH 5.2 and 6.2.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 shifted the [Mg 2+ ] i -dependent inhibition curves to lower concentrations with a single IC 50 of 3.4 µM (Figure 1D). It has been reported that mTRPM7-S1107E mutant is insensitive to [Mg 2+ ] i (Hofmann et al, 2014; Zhelay et al, 2018). Consistently, the spontaneous current activation after break-in was not observed in mTRPM7-S1107E mutant in whole-cell recordings (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%